Review of KDD Cup ‘99, NSL-KDD and Kyoto 2006+ datasets - Protić, Danijela D. (Vojnotehnički glasnik / Military Technical Courier, 2018)
This paper presents a review of three datasets, namely KDD Cup ‘99, NSL-KDD and Kyoto 2006+ datasets, which are widely used in researching intrusion detection in computer networks. The KDD Cup ‘99 dataset consists of five million records, each containing 41 features which can classify malicious attacks into four classes: Probe, DoS, U2R and R2L. The KDD Cup ‘99 dataset cannot reflect real traffic data since it was generated by simulation over a virtual computer network. In the NSL-KDD dataset, redundant and duplicate records form the KDD Cup ‘99 dataset are removed from training and test sets, respectively. The Kyoto 2006+ dataset is built on real three year-network traffic data which are labeled as normal (no attack), attack (known attack) and unknown attack. The Kyoto 2006+ dataset contains 14 statistical features derived from the KDD Cup ‘99 dataset and 10 additional features.
Keywords: intrusion detection; computer network; Kyoto 2006; NSL-KDD; KDD Cup ‘99